Effect of Operating Conditions on Catalytic Gasification of Bamboo in a Fluidized Bed. (18th June 2013) - Wongsiriamnuay, Thanasit; Kannang, Nattakarn; Tippayawong, Nakorn
Abstract : Catalytic gasification of bamboo in a laboratory-scale, fluidized bed reactor was investigated. Experiments were performed to determine the effects of reactor temperature (400, 500, and 600°C), gasifying medium (air and air/steam), and catalyst to biomass ratio (0 : 1, 1 : 1, and 1.5 : 1) on product gas composition, H2 /CO ratio, carbon conversion efficiency, heating value, and tar conversion. From the results obtained, it was shown that at 400°C with air/steam gasification, maximum hydrogen content of 16.5% v/v, carbon conversion efficiency of 98.5%, and tar conversion of 80% were obtained. The presence of catalyst was found to promote the tar reforming reaction and resulted in improvement of heating value, carbon conversion efficiency, and gas yield due to increases in H2, CO, and CH4 . The presence of steam and dolomite had an effect on the increasing of tar conversion.